Impoliteness Strategies in Hate Comments by Netizens Towards K-Pop on Social Media - Balgiz Khairun Nisa; Anna Dewanti; Salimah Salimah (Unipdu Jombang, 2024)
One phenomenon that has become popular in Indonesia is the entry of Korean culture. Korean culture strongly influences various aspects of daily life, one of which is musical taste, namely K-pop music, which is in great demand by young people. However, only some have the same interests, so some netizens comment negatively on K-Pop on Instagram. This study aims to determine the types of impoliteness strategies and functions of impoliteness used by netizens in commenting on K-Pop on Instagram. This study used a descriptive-qualitative method. The writer has collected 37 comments from March 2022 to March 2023. In analyzing the data, the writer used the theory proposed by Culpeper (1996) for the types of impoliteness strategies and Culpeper's (2011) for the functions of impoliteness. The results of the study show that netizens used four impoliteness strategies in their hate comments only: bald on-record impoliteness is 11 comments, positive impoliteness is 12 comments, negative impoliteness is 5, and sarcasm or mock politeness is nine comments. Positive impoliteness becomes the most frequent strategy; furthermore, this study found two functions of impoliteness: affective impoliteness and entertaining impoliteness. Affective impoliteness appears as the dominant function in this study. The study is expected to raise awareness about being wiser when commenting on social media without applying impoliteness strategies.